Analysis of Factors Influencing Marital Satisfaction and External Factors Among Young Students Aged 21-28 Years (Case Study of Students of STDI IMAM SYAFI'I JEMBER) - Akmal Rasyadi Nasution; Mizbahuzzulam Mizbahuzzulam (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2025)
Marital satisfaction is a key factor in maintaining a successful and happy relationship and is a crucial factor that not only determines the quality of a husband and wife's relationship but also affects the overall stability of the family. However, marital satisfaction is often a challenge, especially among young couples aged 21-28. This study employs a qualitative approach using observation and in-depth interviews to gain a deeper understanding of the factors influencing marital satisfaction among young couples aged 21-28 who are registered as students at STDI IMAM SYAFII JEMBER. Marital satisfaction is an assessment conducted by married couples to evaluate the quality of their marriage. The more benefits a couple feels, the more evidence there is that they are satisfied with their marriage. This expert approach highlights that factors such as communication, adaptability to change, conflict management, and role balance are crucial in influencing marital satisfaction. The importance of equality in marriage includes social, educational, and religious equality between husband and wife. Biological relationships are seen as an expression of sexual desire that must be carried out with responsibility and awareness of religious principles. Good communication is the key to building a harmonious relationship, where couples must be able to listen, understand, and respond to each other constructively. Additionally, obedience to the husband based on love, respect, and cooperation is important in creating a harmonious family.